A study on employee perspective towards ISO 9001 Standard in Sinmah Multifeed - Haris, Mohd Ezuwan (2004)
ISO refers to the International Organization for Standardization is a series of international standards for establishing global requirements for quality. The standards were developed to harmonize many national and international standards for quality management systems. ISO is well known for an organization as their work standard to being reorganized by the others especially from consumers and competitors. In America and most of the company around the world ISO is very popular among themselves as steeping-stones to be competitive advantages. For example in military manufacturing standards implemented during World War 2 and as late as 1995 97% of united companies with ISO registration were in manufacturing sector.